AB0845 Technetium-99 conjugated with methylene diphosphonate ameliorates glucocorticoid induced osteoporosis in rats. (15th June 2017) - Shi, L; Ning, Y; Li, J; Hu, F; Zhang, X
Abstract : Background: 99 Tc-MDP has been used in Chinese RA patients for over 15 years and many more studies have focused on this agent in RA. However, the previous studies limited in its effect on the effects of anti-inflammation. As a special form of bisphosphonate, the anti-osteoporotic effect of 99 Tc-MDP is unclear. Objectives: To systematically investigate the effect of technetium-99 conjugated with methylene diphosphonate ( 99 Tc-MDP), an anti-inflammatory drug effective in treating rheumatoid arthritis (RA), on cortical and cancellous bones in glucocorticoid-induced osteoporotic (GIO) rats, as well as comparing the effect of 99 Tc-MDP with that of methylene diphosphonate (MDP). Methods: Forty-eight Sprague-Dawley rats were randomly divided into six groups: blank, negative control, high dose, medium dose, low dose, and positive control groups. After dexamethasone was given to all groups except the blank group to induce osteoporosis, the rats in different groups were treated with saline, MDP, or different doses of Results: Micro-CT analyses showed that: (1) 99 Tc-MDP reversed glucocorticoid induced bone microarchitecture destruction by increasing vBMD, BV/TV, Tb.Th, Tb.N and decreasing BS/BV, Tb.Sp and TBPf; (2) effect of 99 Tc-MDP increased as its dosage increased; and (3) 99 Tc-MDP could improve cortical bone thickness while MDP failed to do so. Micro-CT spatial structure analysis and histology also yielded consistent results, indicating 99 Tc-MDP increased trabecular number and connectivity morphologically. Finally, biomechanics revealed 99 Tc-MDP can enhance the extrinsic stiffness of bone by changing bone geometry. Conclusions: 99 Tc-MDP has anti-osteoporotic effect by improving both cancellous and cortical bone, as well as increasing extrinsic bone stiffness. The dual effect of 99 Tc-MDP, anti-inflammatory and anti-osteoporotic, may suggest a potential clinical application for patients with both GIO and RA. References: Hoes JN, Jacobs JW, Buttgereit F, et al. Current view of glucocorticoid co-therapy with DMARDs in rheumatoid arthritis. Nature reviews Rheumatology 2010;6:693–702. Bijlsma JW. Disease control with glucocorticoid therapy in rheumatoid arthritis. Rheumatology 2012;51 Suppl 4:iv9–13. Acknowledgements: We thank Mr. Kai Gao for providing the rats and Dr. Min Feng for assistance in histological processing of the rats. This work was supported by grants from the Natural Science Foundation of China (81501396 to Dr. Lianjie Shi, and 81302554 to Dr. Fanlei Hu). Disclosure of Interest: None declared